Determinants Affecting Students’ Satisfaction In The Use of Learning Management Systems on Instructional Content, Interaction, and Accessibility - Budi Setiawan; Adrian Rodgers (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
An Learning Management Systems (LMS) is important in boosting knowledge acquisition and information management in the digital world. This investigation examines factors affecting students' satisfaction with each aspect of the LMS instructional content, interaction, and accessibility. Using a quantitative research design, data was collected through an online survey from 104 undergraduate students at Universitas Pendidikan Indonesia. The results showed that over half of the participants were satisfied or highly satisfied with LMS features such as interaction, accessibility, and instructional content. 89.4% of students were satisfied with direct communication from the LMS in interaction. When asked about accessibility, 99% of respondents praised the platform's flexibility and ease of use. For the instructional component, 90 percent of students expressed satisfaction with the quality and accessibility of the materials provided. These findings are significant for educational institutes to enhance learning management system features as per user requirements, enabling more flexible and interactive learning approaches. Research related to learning management systems introduced at a tertiary institution to improve learning effectiveness during the pre- and post-COVID-19 period requires deep analysis, including different particulars shaped in the higher education landscape by the impact of the pandemic. This study significantly contributes to developing technology-based education policies in the digital age.